Feed Intake and Growth Performance of Vietnamese Yellow Calves Fed Silages from Intercropped Maize–Soybean and Guinea Grass - Don V. Nguyen; Beth Penrose; Ngoc B. T. Tran; Huyen T. T. Le; Hong T. Trinh; Stephen Ives (Ruminants)
Combining soybeans with grass or biomass maize in silage holds promise in addressing the nutritional limitations of individual crops, providing a roughage with a good energy–protein balance. This study evaluated the effects of replacing urea-treated rice straw (UTRS) with silages made from intercropped maize–soybean and Guinea grass (GG) in calf diets on feed intake and growth performance. Sixteen native Yellow calves (130.7 ± 16.1 kg live weight and 12.8 ± 2.6 months old) were used; the experiment had a randomised complete block design with four dietary treatments: Treatment 1 (70% UTRS + 30% GG); Treatment 2 (40% UTRS + 30% GG + 30% Guinea grass silage); Treatment 3 (40% UTRS + 30% GG + 30% Guinea grass–soybean silage); and Treatment 4 (40% UTRS + 30% GG + 30% maize–soybean silage). The animals were fed 0.5 kg concentrate per 100 kg live weight daily, with unlimited access to forage and clean water, for 12 weeks after a two-week adaptation. The results indicate that silages containing soybean increased total weight gain and average daily gain (ADG) and decreased feed conversion ratio (FCR); however, silage replacements had no impact on dry matter intake and body conformation, suggesting that Guinea grass–soybean or maize–soybean silage can effectively enhance the ADG and decrease the FCR of growing calves fed UTRS-based diets.